The Cost of Menstrual Cycle in Young Nepali Women: A Cross-Sectional Study - Parajuli, Surya Bahadur; Mishra, Anjali; Luitel, Anish; Sherpa, Tshering Wangchu; KC, Heera (Journal of Lumbini Medical College, 2021)
Introduction: Every woman must have safe access to clean water and menstrual products. They have to spend more or less money to buy menstrual products or to alleviate menstrual symptoms. Cost of a menstrual cycle is often associated with period poverty. We found a research gap on this issue. The objective of this study was to find the cost of menstrual cycle and their perceptions on menstrual cost among young Nepali women. Methods: We conducted a cross sectional study from 15 August 2019 to 15 February 2020. Total enumeration sampling technique was used to enroll 157 female medical students. Ethical clearance was obtained from institutional review committee of Birat Medical College Teaching Hospital. Open data kit (ODK) collect software was used for data collection. The collected data was extracted in Microsoft Excel 2016 and analyzed by SPSS version 23. Results: Majority (33.8%) had menarche at 13 years and 47.8% had regular menstrual cycle. Total average cost of items used in last menstrual period was NPR 480.41 (NPR 40-1850) and lifetime cost was NPR 219066.96. Sanitary pads/ tampons/menstrual cups etc. should cost less money (85.4%) and tax currently put on it should be removed by government (91.1%) were the perceptions of the participants. Conclusion: Menstrual cycle added additional cost in women's life. Participants perceived that cost is high and it should be tax free. Nepal constitution already passed sanitation as basic fundamental right. So, the cost of sanitary items needs to be minimized by removing the government tax.